2010
DOI: 10.1021/ja910688s
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Photocontrol of Protein Localization in Mammalian Cells

Abstract: Precise photochemical control of protein function can be achieved through the site-specific introduction of caging groups. Chemical and enzymatic methods, including in vitro translation and chemical ligation, have been used to photocage proteins in vitro. These methods have been extended to allow the introduction of caged proteins into cells by permeabilization or microinjection, but cellular delivery remains challenging. Since lysine residues are key determinants for nuclear localization sequences, the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
261
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 241 publications
(269 citation statements)
references
References 24 publications
(35 reference statements)
4
261
0
4
Order By: Relevance
“…In addition, we used a modified ONBK to increase the decaging efficiency which was reported previously (Fig. S3B) (Gautier et al, 2010). When modifi ed ONBK was added into liquid cultured stable transgenic strain, NLS TAG ::TagGFP was successfully read through and expressed.…”
Section: Light-induced Protein Translocation By Genetically Encoded Umentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, we used a modified ONBK to increase the decaging efficiency which was reported previously (Fig. S3B) (Gautier et al, 2010). When modifi ed ONBK was added into liquid cultured stable transgenic strain, NLS TAG ::TagGFP was successfully read through and expressed.…”
Section: Light-induced Protein Translocation By Genetically Encoded Umentioning
confidence: 91%
“…ONBK is an unstable lysine derivative, and its ONB group is readily removed upon UV light exposure (Chen et al, 2009;Gautier et al, 2010). To test the functional consequence of ONBK incorporation, we employed two constructs as previously reported: 1) PCKRS (a PylRS mutant)/tRNA pair driven under the promoters of atp-2 and U6-10, respectively; 2) a nuclear localization signal with a lysine mutated to amber stop codon (shorted for NLS TAG ) conjuncted with TagGFP (a homologue of GFP) driven by the promoter atp-2 ( Fig.…”
Section: Light-induced Protein Translocation By Genetically Encoded Umentioning
confidence: 99%
“…Furthermore, the high concentrations of non-incorporated, free unnatural amino acid might be problematic, for example, if fluorescent amino acids are used for live cell imaging. At the moment, the most promising use of this method in cells therefore lies in applications where the free unnatural amino acid does not interfere with downstream applications, such as the photocaging of protein functions, as has recently been demonstrated by photocaging nuclear localization signals in proteins using a lysine bearing a photocleavable protecting group [71 ].…”
Section: Incorporation Of Unnatural Amino Acidsmentioning
confidence: 99%
“…Irradiating the cell with light of appropriate wavelength frees the side chain thereby activating the protein. Photo-caged versions of tyrosine (32), cysteine (33), serine (10) and lysine (34,35) have been genetically incorporated into proteins in bacteria, yeast and mammalian cells [54,75,[83][84][85][86]. As mentioned earlier, photocaged serine has been used to control the phosphorylation state of a serine residue and with it the localisation of a transcription factor in yeast [54].…”
Section: Photo-caged Uaasmentioning
confidence: 99%
“…As mentioned earlier, photocaged serine has been used to control the phosphorylation state of a serine residue and with it the localisation of a transcription factor in yeast [54]. The Chin lab demonstrated that photo-caged lysine can be used to control the recognition of nuclear localisation signals by importins in mammalian cells [85]. Light triggered activation of the NLS facilitated quantifying the kinetics of nuclear transport processes.…”
Section: Photo-caged Uaasmentioning
confidence: 99%